2011
DOI: 10.1007/s00428-011-1127-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a break-apart FISH assay in the diagnosis of Xp11.2 translocation renal cell carcinoma

Abstract: Xp11.2 translocation renal cell carcinoma (RCC) is a rare subtype of RCC predominantly reported in young patients. It results from gene fusions between the transcription factor E3 (TFE3) gene, which is located on chromosome Xp11.2, and various fusion partners. Recently, a dual color, break-apart fluorescence in situ hybridization (FISH) assay to detect Xp11.2 translocation was reported. We performed this study to evaluate the usefulness of the FISH assay in the diagnosis of Xp11.2 translocation RCC using a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Although RT-PCR can provide exact information of gene rearrangement, it is often technically challenging [16]. TFE3 break-apart FISH assay is useful in formalin-fixed, paraffin-embedded tissue for detection of Xp11.2 RCCs in clinical settings [25,26]. Hence, FISH was adopted in our study and clinical work.…”
Section: Resultsmentioning
confidence: 99%
“…Although RT-PCR can provide exact information of gene rearrangement, it is often technically challenging [16]. TFE3 break-apart FISH assay is useful in formalin-fixed, paraffin-embedded tissue for detection of Xp11.2 RCCs in clinical settings [25,26]. Hence, FISH was adopted in our study and clinical work.…”
Section: Resultsmentioning
confidence: 99%
“…4,6,9,14,47 Xp11.2 renal cell carcinoma can also be misdiagnosed as papillary renal cell carcinoma when cytoplasmic clearing is present because of degeneration associated with hemosiderin deposition as well as when the Xp11.2 renal cell carcinoma has prominent eosinophilic cytoplasm that can mimic type 2 papillary renal cell carcinoma. 3,4,6,9,14 IHC is a potential screening tool for Xp11.2 renal cell carcinoma but does not have sufficient sensitivity or specificity to establish TFE3 rearrangement; true TFE3 disruption was confirmed by FISH only in four of the nine (44%) well-characterized renal cell carcinoma tumors that had moderate-to-strong nuclear TFE3 immunoreactivity in each of two recent studies, 28,29 and fixation-related artifacts have been reported, such as an affinity for the edges as well as variability in antibody batch performance. 30,48,49 Similar findings occurred for alveolar soft part sarcoma where only 22 of the 24 cases of TFE3/ASPSCR1 confirmed by FISH were positive by IHC and, importantly, TFE3 immunoreactivity was also noted in two of five non-alveolar soft part sarcoma neoplasms (granular cell tumors) that were negative by FISH.…”
Section: Discussionmentioning
confidence: 99%
“…To address diagnostically challenging cases of alveolar soft part sarcoma and Xp11.2 renal cell carcinoma, consideration of clinical presentation and histopathologic features has historically been supplemented by immunohistochemistry (IHC) for TFE3 protein; however, the antibody is limited in sensitivity and specificity, [28][29][30][31][32] which may be influenced by the method employed. 33 A genetic approach is therefore required to confirm TFE3 rearrangement.…”
mentioning
confidence: 99%
“…EMA can be focally positive, and there is a variable expression of vimentin, AMACR, Melan-A, and HMB45. The diagnosis is definitely proven by the demonstration of TFE3 or TFEB expression [26] and/or by evidencing the gene rearrangement by FISH assay [35].…”
Section: Papillary Renal Cell Carcinomamentioning
confidence: 99%